BISAC: Book industry standards and communications - Martínez-Ávila, Daniel [UNESP] (My University, 2016)
The BISAC Subject Headings List is a standard used to categorize books in the book industry of the United States. Since the second half of the 2000s, several public libraries in the United States have experimented with BISAC as an alternative classification system to the Dewey Decimal Classification (DDQ. The system has been used by Google Books and other electronic platforms. This article reviews its main characteristics, structure and display, development and revision process, epistemology and approach to KO, use in libraries, and future.
Keywords: BISAC; BISG; Book industry; Library classification; Subject headings